Reactive oxygen species–mediated switching expression of MMP-3 in stromal fibroblasts and cancer cells during prostate cancer progression - Chia-Ling Hsieh (Nature Portfolio, 2017)
Abstract Studies on the aberrant control of extracellular matrices (ECMs) have mainly focused on the role of malignant cells but less on that of stromal fibroblasts during cancer development. Herein, by using paired normal and prostate cancer-associated stromal fibroblasts (CAFs) derived from a coculture cell model and clinical patient samples, we demonstrated that although CAFs promoted prostate cancer growth, matrix metalloproteinase-3 (MMP-3) was lower in CAFs but elevated in prostate cancer cells relative to their normal counterparts. Furthermore, hydrogen peroxide was characterized as the central modulator for altered MMP-3 expression in prostate cancer cells and CAFs, but through different regulatory mechanisms. Treatment of CAFs but not prostate cancer cells with hydrogen peroxide directly inhibited mmp-3 promoter activity with concomitant nuclear translocation of nuclear factor-κB (NF-κB), indicating that NF-κB is the downstream pathway for the transcriptional repression of MMP-3 in CAFs. Hydrogen peroxide reduced thrombospondin 2 (an MMP-3 suppressor) expression in prostate cancer cells by upregulating microRNA-128. To the best of our knowledge, this is the first study to demonstrate the crucial role of reactive oxygen species in the switching expression of MMP-3 in stromal fibroblasts and prostate cancer cells during tumor progression, clarifying how the tumor microenvironment modulates ECM homeostasis control.